Dual drug delivery system for targeting H. pylori in the stomach: preparation and in vitro characterization of amoxicillin-loaded Carbopol® nanospheres - Harsha S (International Journal of Nanomedicine, 2012)
Sree HarshaDepartment of Pharmaceutical Sciences, College of Clinical Pharmacy, King Faisal University, Al-Asha, Saudi ArabiaBackground and methods: A dual (immediate/sustained-release) oral amoxicillin suspension was developed as a new dosage form to eradicate Helicobacter pylori. Carbopol®-loaded amoxicillin nanospheres could bind with the mucosa after delivery to the stomach and could increase the efficiency of the drug, providing both an immediate and a sustained action.Results: The objective of this research was to develop amoxicillin nanospheres using a spray-drying technique and to investigate such features as their particle size, drug content, percentage yield, surface morphology, in vitro release, and stability. The nanospheres had a particle size range of 280–320 nm after optimizing the preparation method using a central composite design. The drug content and percentage yield was 85.3% ± 0.7% and 92.8% ± 0.9%, respectively. The in vitro release profile of the amoxicillin nanospheres was consistent with a Korsmeyer-Peppas pattern, and the release after one hour was 19%, while for the original drug, amoxicillin, under the same conditions, 90% was released in the first 30 minutes.Conclusion: The nanospheres used in this study enabled controlled release of amoxicillin over an extended period of time for up to 12 hours and the formulation was stable for 12 months.Keywords: nanospheres, nano spraydryer, optimization, amoxicillin, Helicobacter pylori